2018
DOI: 10.1093/ajae/aay012
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Extension and Technology Adoption for Food Security: Evidence from Uganda

Abstract: We evaluate causal impacts of a large-scale agricultural extension program for smallholder women farmers on technology adoption and food security in Uganda through a regression discontinuity design that exploits an arbitrary distanceto-branch threshold for village program eligibility. We find eligible farmers used better basic cultivation methods, achieved improved food security. Given minimal changes in adoption of relatively expensive inputs, we attribute these gains to improved cultivation methods that requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
65
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 64 publications
8
65
0
3
Order By: Relevance
“…The amount of “learning from others” depends on existing social networks (Rogers ). This has stimulated much interest on designing policies that can make use of social networks to speed up the adoption of new technologies (Beaman et al ; Pan, Smith, and Sulaiman ; BenYishay and Mobarak ; Omotilewa, Ricker‐Gilbert, and Ainembabazi ; Läpple, Barham, and Chavas Forthcoming). In the context of Irish dairy farms, Läpple, Barham, and Chavas (Forthcoming) document the positive impact of extension services on dairy herd size, intensification and specialization.…”
Section: Innovations and Technology Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of “learning from others” depends on existing social networks (Rogers ). This has stimulated much interest on designing policies that can make use of social networks to speed up the adoption of new technologies (Beaman et al ; Pan, Smith, and Sulaiman ; BenYishay and Mobarak ; Omotilewa, Ricker‐Gilbert, and Ainembabazi ; Läpple, Barham, and Chavas Forthcoming). In the context of Irish dairy farms, Läpple, Barham, and Chavas (Forthcoming) document the positive impact of extension services on dairy herd size, intensification and specialization.…”
Section: Innovations and Technology Adoptionmentioning
confidence: 99%
“…They point to the potential value of public and private coordination in directly and indirectly fostering productivity growth. Applied to Ugandan farmers, Pan, Smith, and Sulaiman () show how extension services can contribute to increasing agricultural production and improving food security. BenYishay and Mobarak () ran a Randomized Controlled Trial in Malawi and showed that offering performance‐based (financial) incentives to some specific farmers could be a cost‐effective way to disseminate information about a new technology, in particular in contexts where extension services are short of staff.…”
Section: Innovations and Technology Adoptionmentioning
confidence: 99%
“…The positive effects, however, emerge over a longer-time period such that women were rarely among the early adopters. Pan et al (2018) explore similar issues in Uganda with women model farmers who facilitate training and access to hybrid maize seed, particularly for fellow women smallholder farmers. While Pan et al (2018) only look at household-level outcomes, they do find significant positive effects of the intervention on the adoption of low-cost recommended agronomic practices and inputs, and on household food security.…”
Section: Intra-household Information Asymmetriesmentioning
confidence: 99%
“…The problems that emanate from agriculture at grass roots level are identified by Extension Personnel and related to the researchers for plausible solutions [4][5]. The researchers then provide information through recommendationsthe leaders who distribute improved technologies [6].…”
Section: Introductionmentioning
confidence: 99%